Canarium odontophyllum Miq. (Dabai) Leaf Phytoextracts and Their Medicinal Properties - Muhammad Wahizul Haswan, Abdul Aziz; Siti Fathiah, Masre; Dayang Fredalina, Basri; Ahmad Rohi, Ghazali (Universiti Putra Malaysia Press, 2022)
Canarium odontophyllum Miq., renowned locally as “dabai,” is an endemic plant in Sarawak, Malaysia. Most people, especially in rural areas, consume this plant to maintain their health. A few medicinal studies have investigated C. odontophyllum Miq.’s biological properties to substantiate its use as nutraceuticals and health supplements. Crude extracts from C. odontophyllum Miq. demonstrated various medicinal properties, including antibacterial, antimalarial, antioxidant, anticancer, antidiabetic, and antihypertensive. In addition, numerous phytoextracts studies have revealed the existence of a variety of beneficial compounds, including flavonoids, tannins, and terpenoids. However, despite various biological activities of C. odontophyllum Miq., there is currently no analysis summarizing the medicinal properties of its leaf. Thus, this short communication attempts to narrate the medicinal properties of C. odontophyllum Miq. leaf and their phytoextracts responsible. In conclusion, we summarized C. odontophyllum Miq. leaf promising therapeutic effects with their phytoextracts and a step closer to developing it as potential nutraceuticals and health supplements to fulfill social interest.